Preliminary report on the provision of HIV care to war refugees with HIV who are migrating from Ukraine: data from the ECEE Network Group - Kowalska, Justyna D; Rukhadze, Nino; Sojak, Lubomir; Bociaga-Jasik, Monika; Sedlacek, Dalibor; Matulionyte, Raimonda; Jilich, David; Yancheva, Nina; Papadopoulos, Antonios; Rozplochowski, Blazej; Patrascu, Raluca; Aimla, Kersti; et al. (AIDS (London, England), 2022)
The ECEE Network Group investigated early provision of HIV care to war refugees migrating from Ukraine in Central and Eastern Europe (CEE) through an online survey. Fourteen countries admitting war refugees from Ukraine on March 31, 2022, completed the survey. Most centers (86%) organized provision of same day antiretroviral therapy (ART) for at least 30 days (77%), but indicated that it may affect the local HIV care. CEE countries put effective emergency mechanisms, which need continuation with international support.
Keywords: východní Evropa; Evropa; HIV infekce; Humans; HIV Infections; Refugees; Ukraine; Ukrajina; Europe; Europe, Eastern; lidé; uprchlíci